Endozoicomonas Are Specific, Facultative Symbionts of Sea Squirts - Schreiber, Lars; Kjeldsen, Kasper U.; Funch, Peter; Jensen, Jeppe; Obst, Matthias; López-Legentil, Susanna; Schramm, Andreas (Frontiers in Microbiology, 2016)
Ascidians are marine filter feeders and harbor diverse microbiota that can exhibit a high degree of host-specificity. Pharyngeal samples of Scandinavian and Mediterranean ascidians were screened for consistently associated bacteria by culture-dependent and -independent approaches. Representatives of the Endozoicomonas (Gammaproteobacteria, Hahellaceae) clade were detected in the ascidian species Ascidiella aspersa, A. scabra, Botryllus schlosseri, Ciona intestinalis, Styela clava, and multiple Ascidia/Ascidiella spp. In total, Endozoicomonas was detected in more than half of all specimens screened, and in 25% to 100% of the specimens for each species. The retrieved Endozoicomonas 16S rRNA gene sequences formed an ascidian-specific subclade, whose members were detected by fluorescence in situ hybridization (FISH) as extracellular microcolonies in the pharynx. Two strains of the ascidian-specific Endozoicomonas subclade were isolated in pure culture and characterized. Both strains are chemoorganoheterotrophs and grow on mucin (a mucus glycoprotein). The strains tested negative for cytotoxic or antibacterial activity. Based on these observations, we propose ascidian-associated Endozoicomonas to be commensals, living off the mucus continuously secreted into the pharynx. Members of the ascidian-specific Endozoicomonas subclade were also detected in seawater from the Scandinavian sampling site, which suggests acquisition of the symbionts by horizontal transmission. The combined results indicate a host-specific, yet facultative symbiosis between ascidians and Endozoicomonas.